2018
DOI: 10.1111/mmi.14076
|View full text |Cite
|
Sign up to set email alerts
|

PcrX, an sRNA derived from the 3′‐ UTR of the Rhodobacter sphaeroides puf operon modulates expression of puf genes encoding proteins of the bacterial photosynthetic apparatus

Abstract: Facultative phototrophic bacteria like Rhodobacter sphaeroides can produce ATP by anoxygenic photosynthesis, which is of advantage under conditions with limiting oxygen. However, the simultaneous presence of pigments, light and oxygen leads to the generation of harmful singlet oxygen. In order to avoid this stress situation, the formation of photosynthetic complexes is tightly regulated by light and oxygen signals. In a complex regulatory network several regulatory proteins and the small non-coding RNA PcrZ co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 46 publications
2
24
0
Order By: Relevance
“…The majority of bacterial sRNAs so far identified are encoded within IGRs and are independently transcribed (Vogel et al ., 2003; Kawano et al ., 2005; Loh et al ., 2009; Chao et al ., 2012; Chao and Vogel, 2016; Dar and Sorek 2018). Nevertheless, a few 3′‐UTR‐derived sRNAs (Kawano et al ., 2005; Kim et al ., 2014; Chao and Vogel, 2016; Chao et al ., 2017; Eisenhardt et al ., 2018; Miyakoshi et al ., 2019), 5′‐UTR‐derived sRNAs (Kawano et al ., 2005; Drecktrah et al ., 2018), and protein coding region‐derived sRNAs (called decay‐generated noncoding RNAs [decRNAs]) (Dar and Sorek, 2018) have been reported in different bacterial species. Surprisingly, our study demonstrated that, in Xcc, mRNA processing is the primary source of cellular sRNA, suggesting a close link between sRNA biogenesis and mRNA decay.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of bacterial sRNAs so far identified are encoded within IGRs and are independently transcribed (Vogel et al ., 2003; Kawano et al ., 2005; Loh et al ., 2009; Chao et al ., 2012; Chao and Vogel, 2016; Dar and Sorek 2018). Nevertheless, a few 3′‐UTR‐derived sRNAs (Kawano et al ., 2005; Kim et al ., 2014; Chao and Vogel, 2016; Chao et al ., 2017; Eisenhardt et al ., 2018; Miyakoshi et al ., 2019), 5′‐UTR‐derived sRNAs (Kawano et al ., 2005; Drecktrah et al ., 2018), and protein coding region‐derived sRNAs (called decay‐generated noncoding RNAs [decRNAs]) (Dar and Sorek, 2018) have been reported in different bacterial species. Surprisingly, our study demonstrated that, in Xcc, mRNA processing is the primary source of cellular sRNA, suggesting a close link between sRNA biogenesis and mRNA decay.…”
Section: Discussionmentioning
confidence: 99%
“…However, RNase E also has important roles for sRNA biogenesis and maturation. Several sRNAs are known to be produced from the 3ʹ region of protein coding genes, either through usage of an internal promoter or by RNase E catalyzed mRNA processing [11][12][13], and regulatory roles for sRNAs generated through the latter mechanism were demonstrated in various species including E. coli and Salmonella [14][15][16][17]. An additional class of sRNAs is autonomously transcribed, but undergoes maturation.…”
Section: Introductionmentioning
confidence: 99%
“…Many cellular oligonucleotides are products of endonuclease cleavage (Davis and Waldor, 2007;Papenfort et al, 2009;Chao et al, 2017), and some short fragments of tRNAs are proven to be functional (Lalaouna et al, 2015a,b;Diebel et al, 2016;Swiatowy and Jagodzińśki, 2018). In recent years it has been also witnessed for both bacteria and higher organisms that 3 ′ -terminal regions of mRNAs can also be sources of short regulatory RNAs specifically processed by RNAse E (Eisenhardt et al, 2018;Miyakoshi et al, 2019;Hoyos et al, 2020;Wang et al, 2020). Thus, it is likely that the processing of many RNAs with well-established function plays a specific role in living cells by providing short oligonucleotides for diverse regulatory networks.…”
Section: Introductionmentioning
confidence: 99%